Inferior oblique sparing brachytherapy plaque placement for juxtafoveal peripapillary choroidal melanoma - Neiwete Lomi; Deepsekhar Das; Bhavna Chawla; Ananya Herle (Indian Journal of Ophthalmology)
Plaque brachytherapy has been used in the management of small to medium-sized choroidal melanomas for the past few decades. As the inferior oblique muscle lies in close relation to the macula, the placement procedure of plaques often involves sacrificing the inferior oblique muscle, especially in cases of macular or perimacular choroidal melanomas. In this study, we have described a simple maneuver to preserve the inferior oblique muscle.